Mekanisme Good Corporate Governance, Sustainability Report, dan Kinerja Keuangan Perusahaan - Puspa Dewi, Luh Gde Pasek; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi; Vol 34 No 2 (2024)DO - 10.24843/EJA.2024.v34.i02.p11, 2024)
This research was conducted to determine the relationship between good corporate governancemecanismand sustainability reports on company financial performance. Research data collection was carried out on companies that were registered on the Indonesia Stock Exchange (IDX) in the 2018-2021 research period with a population of all companies in the raw goods and energy sector. There were 18 companies that published sustainability reports and annual reports in that period. Samples were taken as many as 13 companies with 38 observation samples through purposive sampling. Multiple linear regression analysis was used as a data analysis technique. The results of the research observations produce good corporate governance by proxies for the board of directors and managerial ownership, as well as sustainability reports that have a positive influence on company performance. Meanwhile, good corporate governance with audit committee proxies and institutional ownership has no effect on company performance. Keywords:Good Corporate Governance; Sustainability Report; Company Performance; Return on Assets.